The Correlation of Self-efficacy Towards Students’ Writing Skills at Eleventh Grade Students of Senior High School 9 Jambi City - Naila, Niken Dwi; Wennyta, Wennyta; Yurni, Yurni (Universitas Batanghari Jambi, 2023)
The purpose of this research was to find out whether there is any correlation of self-efficacy toward students’ writing skills at eleventh grade students of Senior High School 9 Jambi City. This research used quantitative method with correlational research as the design. The population in this research was eleventh grade students of Senior High School 9 Jambi City with total 240 students and the sample in this research was 71 students taken by using simple random sampling technique. The technique data collection in this research using questionnaire and writing test. The data were analyzed by using person product moment correlation coefficient by SPSS 21. The result of the correlation coefficient (r) was 0.690 and that was higher than the rtable 0.230 on significant level 5%. The result of hypothesis test was 0.000 < 0.05. It means that Ho was rejected and Ha was accepted because the value of Sig. is less than the 0.05. In conclusion, there is significant correlation of self-efficacy towards students’ writing skills at eleventh grade students of Senior High School 9 Jambi City.